PROBLEMATIKA KEMAMPUAN MEMBACA AL-QUR’AN PESERTA DIDIK SMA DAN PENGEMBANGAN METODE SEDAYU SEBAGAI SOLUSI PEMBELAJARAN PAI - Ratna Sukma Dewi; Siti Nuraisyah; Itim Patimah; Resi Purnama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to read the Qur’an is a fundamental competence that must be possessed by Muslim students in Islamic Religious Education (PAI). However, empirical conditions indicate that Qur’anic reading skills among senior high school students remain problematic. This study aims to describe students’ Qur’anic reading abilities, identify existing problems and influencing factors, and examine the development of the Sedayu method as a learning solution. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving Islamic Religious Education teachers and students. Data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation techniques. The results indicate that students’ Qur’anic reading abilities vary, and some students still lack mastery of pronunciation, fluency, and basic tajwid rules. These problems are influenced by internal and external factors, such as low motivation, lack of practice, limited instructional time, and less adaptive teaching methods. The Sedayu method contributes positively to improving students’ participation, confidence, and fluency. Therefore, this method is considered relevant and applicable in improving Qur’anic reading skills in PAI learning.